Agama, Moral dan Etika: Perspektif Dialektika dan Implikasinya dalam Ekonomi - Djakfar, Muhammad (el Harakah: Jurnal Budaya Islam, 2006)
Religion, moral and ethics are institution which have the same learning wisdom value and justice. They undergo dialectic in daily life. Otherwise, dialectic result will never be meaningful without being connected with contextual problem, such as economy. This paper explores how the dialectic implication in economy activities is. There are 2 patterns of thinking. First, Al-Ghozali's pattern emphasizes on theology strength than reason, because it is based on Al- Qur'an and Hadist. This pattern is followed by Yusuf Qardhawi, Mustaq Ahmad and M. Quraish Shihab. Second, a pattern directed by E.Kant uses critical power and sharp analytical. This pattern is followed by Weber, Pratley and Rowland. For appearing the growth of epoch, both of the patterns need to be evolved in order to be more optimal in guiding further economy activities. However it is, economic progress needs knowledge and spiritual power. Agama, moral dan etika adalah institusi yang memiliki nilai kearifan dan keadilan pembelajaran yang sama. Mereka menjalani dialektika dalam kehidupan sehari-hari. Jika tidak, hasil dialektika tidak akan pernah berarti tanpa berhubungan dengan masalah kontekstual, seperti ekonomi. Makalah ini membahas bagaimana implikasi dialektika dalam kegiatan ekonomi. Ada 2 pola pemikiran. Pertama, pola Al-Ghozali lebih menekankan pada kekuatan teologi daripada alasan, karena didasarkan pada Al-Qur'an dan Hadis. Pola ini diikuti oleh Yusuf Qardhawi, Mustaq Ahmad dan M. Quraish Shihab. Kedua, pola yang diarahkan oleh E.Kant menggunakan kekuatan kritis dan analisis yang tajam. Pola ini diikuti oleh Weber, Pratley dan Rowland. Untuk menampakkan pertumbuhan zaman, kedua pola tersebut perlu dikembangkan agar lebih optimal dalam membimbing kegiatan ekonomi lebih lanjut. Namun, kemajuan ekonomi membutuhkan pengetahuan dan kekuatan spiritual.